Technical Choices in Pediatric Living Donor Liver Transplantation: The Path to Reduce Vascular Complications and Improve Survival. Issue 12 (21st November 2020) - Neto, João Seda; Fonseca, Eduardo A.; Vincenzi, Rodrigo; Pugliese, Renata; Benavides, Marcel R.; Roda, Karina; Porta, Gilda; Miura, Irene K.; Porta, Adriana; Borges, Christian; Baggio, Vera; Feier, Flavia H.; et al.
Abstract : Pediatric living donor liver transplantation (PLDLT) is a successful therapeutic option for children with chronic and acute liver disease. After early transplant results, many technical advancements were introduced in the field to reduce the rate of complications and improve survival. The aim of this study is to present the outcomes of 975 primary PLDLTs in 3 periods: initial practice (period 1, 29 patients, January 1995 to December 1999), second period (period 2, 331 patients, January 2000 to December 2009), and third period (period 3 [P3], 615 patients, January 2010 to September 2019). Among the technical refinements introduced in P3 are the use of hyperreduced left lateral segment grafts, abdominal wall prosthetic mesh closure, double hepatic artery anastomosis, and increased use of vascular grafts for portal vein reconstruction. The outcomes included significant reductions of hepatic artery thrombosis (HAT), early portal vein thrombosis (EPVT), and retransplantation, with better patient and graft survival in P3. Additional analyses showed that the factors independently associated with worse 90‐day patient survival were HAT, EPVT, and increasing Pediatric End‐Stage Liver Disease score. In conclusion, the introduction of technical refinements in P3, in addition to improvements in patient care, determined a reduction in EPVT, HAT, and retransplantation. Consequently, patient and graft survival rates increased in all time points studied.